Assessment Centres - Reconciling Academic Literature vis-a-vis Current Industrial Practices - Bhalerao, Hemangi; Aggarwal, Raksha (SFIMAR Research Review, 2010)
Assessment Centres are rapidly gaining popularity across the globe. They have the potential to facilitate growth and at the same time can be a cause of concern. The academic literature is replete with various studies about the predictive validity of the assessment centers and the necessity of exercising caution to ensure that they are legally defensible. Today, assessment centers are proliferating rapidly and we see more and more organizations using their services. The purpose of this paper to bring forth the wide disparity between theory and practice with regards to assessment centers. The author has studied current assessment centre practices in various organizations in India and evaluated them with regards to the academic literature. Recommendations have been made not only from legal perspective but also on ethical grounds.